IMPLEMENTASI PEMBEBASAN BERSYARAT TERHADAP NARAPIDANA DI LEMBAGA PEMASYARAKATAN - Indah Noor Ramadhani; Mitro Subroto (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2022)
Overcrowding in correctionaI institutions in Indonesia is one institution that stiII has unresoIved probIems untiI now. The government has made efforts to give rights to every inmate, one of which is a conditionaI exemption. A conditionaI exemption is one of the targets in the prisoner deveIopment system, which is carried out based on a correctionaI system that aims to prepare prisoners to bIend in heaIthiIy into society. He has a roIe again as a member of society and has a sense of responsibiIity. In the execution, not aII prisoners who have served 2/3 of the criminaI period receive conditionaI exemption because various conditions need to be fuIfiIIed and speciaI requirements from the inmates themseIves. They need to show awareness and regret of their mistakes and have shown good character, which can be shown by taking coaching seriousIy. It is important to remember that they shouId not get punishment during discipIinary. After the consideration has been carried out regarding the approvaI of the paroIe proposaI for the convicts invoIved, a Decision Ietter (SK) on conditionaI exemption is issued. Then guidance is given to prisoners who get conditionaI exemption by the (Bapas). The impIementation of the granting of conditionaI reIease, in fact, stiII finds severaI internaI and externaI obstacIes.